TQM in Engineering Education through Meaningful Student Evaluation and Faculty Appraisal - Bhattacharya, S. K. (Journal of Engineering Education Transformations, 2007)
Engineering Education in India has witnessed tremendous growth during the past decade. This sudden expansion has led to the problem of maintenance of desired quality. External controlling authorities have been making some effort through their "equality inspectors" having only marginal result. Internal motivation only can lead to achievement and maintenance of quality. While TQM techniques call be tried in education by taking a holistic view of the system, the critical components of the system, viz faculty development and the student evaluation system need to be given priority. Factors which would influence internal motivation have also to be looked into.